(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The gathering and use of PHI is crucial in the current age of healthcare for the purposes ofmedical research, clinical decision making, and the development of healthcare technology. The secondaryuse of personal health information has arisen as a serious ethical, legal, and societal problem with therising digitalization of medical records and the expansion of data-driven healthcare systems. In thisarticle, we explore the varied perspectives of patients on the secondary use of their health records. Theterm personal health information refers to a wide range of details about an individual, such as theirmedical history, diagnosis, treatment plan, test findings, and even their genetic makeup. Researchers inthis report spoke in-depth with contemporary Saudi healthcare consumers through semi-structuredinterviews. The interviews focused on a wide range of information-related topics, each of which wasintroduced via a fictional scenario. Key issues for providers and researchers to reflect on when utilizingpatient health information for secondary purposes have been outlined in this study to guarantee thatsuch usage is patient-informed.